2008
DOI: 10.1248/cpb.56.941
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cytotoxicity Studies of Novel [1,2,4]Triazolo[1,5-a]pyrimidine-7-amines

Abstract: 941Cancer is a disease of striking significance in the world today. It represents the second leading cause of human mortality after cardiovascular diseases. In order to develop more effective and reliable anticancer agents, a large number of compounds bearing nitrogen-containing fused heterocyclic skeletons, such as 4-anilinoquinazolines, pyrazolopyrimidines, triazolopyrimidines, pyrrolopyrimidines, pyrazolopyridazines and imidazopyrazines, have been discovered particularly and many of them exhibited excellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…They are used as optical brightening agents, as antioxidants, as corrosion inhibitors and as additives with a variety of other functions. www.bosaljournals/chemint/ editorci@bosaljournals.com as antimicrobial, analgesic, anti-Inflammatory, anti convulsant, anti-neoplastic, anti-malarial, anti-viral, antiproliferative, and anti-cancer activities (Zhou and Wang, 2012;Ebdrup et al, 2004;Sun et al, 2006;Upadhayaya et al, 2009;Vishnumurthy et al, 2011;Wuest et al, 2009;Zhai et al, 2008;Zhu et al, 2008). The importance of triazole derivatives lies in the field that these have good position in heterocyclic chemistry, due to its various biological activities.…”
Section: Discussionmentioning
confidence: 99%
“…They are used as optical brightening agents, as antioxidants, as corrosion inhibitors and as additives with a variety of other functions. www.bosaljournals/chemint/ editorci@bosaljournals.com as antimicrobial, analgesic, anti-Inflammatory, anti convulsant, anti-neoplastic, anti-malarial, anti-viral, antiproliferative, and anti-cancer activities (Zhou and Wang, 2012;Ebdrup et al, 2004;Sun et al, 2006;Upadhayaya et al, 2009;Vishnumurthy et al, 2011;Wuest et al, 2009;Zhai et al, 2008;Zhu et al, 2008). The importance of triazole derivatives lies in the field that these have good position in heterocyclic chemistry, due to its various biological activities.…”
Section: Discussionmentioning
confidence: 99%
“…SAR is briefly represented in Figure 10. [43] In 2012, Huang and co-workers described a simplistic method for the synthesis of novel 7-arylandrostano [17,16-d] [1,2,4]triazolo [1,5-a]pyrimidine analogs and performed in vitro anticancer activity against EC9706 (human esophageal carcinoma), PC-3 (human prostatic carcinoma), and MCF-7 (human breast carcinoma) cell lines. Among the series, compounds 10 and 11 bearing isopropyl group on the phenyl ring of the main scaffold displayed promising activity against all the cell lines.…”
Section: Anti-cancer Activitymentioning
confidence: 99%
“…From the SAR, it was observed that substitution decoration of the side chain at the C‐2 position and trifluoromethylaniline substitution at the C‐7 position are essential for potent activity. SAR is briefly represented in Figure 10 [43] …”
Section: Pharmacological Activities With Sar Studiesmentioning
confidence: 99%